Human intestinal epithelial and smooth muscle cells are potent producers of IL-6 - Edmond K. Ng; Ninder Panesar; Walter E. Longo; Marc J. Shapiro; Donald L. Kaminski; Kym C. Tolman; John E. Mazuski (Hindawi Limited, 2003)
Background: Interleukin-6 (IL-6), a pluripotent cytokine, has traditionally been considered the product of proinflammatory cells. However, many other cell types have been shown to produce IL-6. Since intestinal inflammation is commonly associated with a vigorous systemic inflammatory response, we hypothesized that intestinal epithelial and smooth muscle cells might contribute to that response by producing IL-6. We therefore studied the capacity of differentiated human intestinal epithelial and smooth muscle cell lines to produce IL-6 in response to various proinflammatory stimuli.